ANALISIS SEMIOTIKA ROLAND BARTHES DALAM NOVEL PASUNG JIWA KARYA OKKY MADASARI - Zahra, Safira Amelia; Supena, Ahmad (Jurnal Bahastra, 2024)
This research aims to describe the meaning of denotation, connotation and myth contained in several quotations from the novel "Pasung Jiwa" by Okky Madasari. The method used in this research is a qualitative research method using library study data collection techniques and collecting data using reading and note-taking techniques. The research results from the analysis of the novel "Pasung Jiwa" by Okky Madasari are that there are denotational meanings, connotative meanings and myths contained in the text of the novel quotations which describe family relationships, law, economic problems, mental health and political power. The purpose of this research is so that readers can understand the meaning of denotation, connotation and myth contained in the novel "Pasung Jiwa". By understanding this meaning, readers can understand the important messages conveyed by the author regarding social, political and cultural situations.